Flavanoids from Dalea elegans: chemical reassignment and determination of kinetics parameters related to their anti-tyrosinase activity - Peralta, Mariana Andrea (2014)
In the first chemical investigation developed on the species Dalea elegans twenty years ago, the occurrence of two prenylated derivatives of pinocembrin was reported: 2′,4′-dihydroxy-5′-(1‴,1‴-dimethylallyl)-6-prenylpinocembrin (6PP) given as a new structure in this family of compounds, and another derivative of already known structure, 6-prenylpinocembrin (6P). In the present paper, their structures were again analyzed by using spectroscopic techniques, especially 2D NMR. Based on the evidence obtained it is proposed the reassignment of both flavanones as: 2′,4′-dihydroxy-5′-(1‴,1‴-dimethylallyl)-8-prenylpinocembrin (8PP) for the first and 8-prenylpinocembrin (8P) for the last. Additionally, triangularin, demethoxymatteucinol, comptonin and 7-hydroxy-5-methoxy-6,8-dimethylflavanone were isolated from aerial parts of D. elegans and informed by the first time for this species. All of these compounds were evaluated in vitro in relation to the antityrosinase effect by using a spectrophotometric method. Compound 8PP (IC50 2.32 ± 0.01 μM) exhibited the most potency and was two times more active than Kojic acid (IC50 4.93 ± 0.01 μM) used as a positive control. Triangularin also has shown an important inhibitory activity. Kinetic studies were performed for both compounds. Hence, new tyrosinase inhibitors with potential applications in pharmacy and cosmetic industry are presented.